Inside Front cover: Rapid detection of trace Cu2+ using an l‐cysteine based interdigitated electrode sensor integrated with AC electrokinetic enrichment. Issue 20 (15th October 2019) - Qi, Haochen; Zhao, Meiqi; Liang, Huaguo; Wu, Jayne; Huang, Zhengfeng; Hu, Anming; Wang, Jian; Lu, Yingchun; Zhang, Jian
Abstract : DOI:10.1002/elps.201900169 The cover picture shows the accelerated capture of copper ions byl ‐cysteine modificated interdigital electrode. Microflows induced by AC electrothermal effect convect copper ions toward the electrodes to enhance the capture of target analytes by L‐cysteine probes. By monitoring the interfacial capacitance of the sensor, this sensor reaches a limit of detection at femtomolar level in 30 seconds, with a wide linear range of (5fM∼0.5nM). Detection of copper ions in tap water demonstrates the feasibility of this sensor for practical applications.